Sound art revisited - Licht, Alan (Bloomsbury Academic, Bloomsbury Publishing Inc, 2019)
"The first edition of Sound Art Revisited (published as Sound Art: Beyond Music, Between Categories) served as a groundbreaking work toward defining this emerging field, and this fully updated volume significantly expands the story to include current research since the book's initial release. Viewed through a lens of music and art histories rather than philosophical theory, it covers dozens of artists and works not found in any other book on the subject. Locating sound art's roots across the centuries from spatialized church music to the technological developments of radio, sound recording, and the telephone, the book traces the evolution of sound installations and sound sculpture, the rise of sound art exhibitions and galleries, and finally looks at the critical cross-pollination that marks some of the most important and challenging art with and about sound being produced today."--Bloomsbury Publishing.